Experimental investigations on in-cylinder flame and emission characteristics of butanol-gasoline blends in SI engine using combustion endoscopic system - Kumaravel, S.; Saravanan, C. G.; Raman, Vallinayagam; Vikneswaran, M.; Sasikala, J.; Josephin, J. S. Femilda; Varuvel, Edwin Geo (Elsevier, 2024)
The objective of this study is to characterize the in-cylinder flames of butanol-gasoline blends in a spark ignition (SI) engine. The experiments were performed using butanol-gasoline blends prepared in the ratio of 10:90, 20:80, and 30:70 by volume. The in-cylinder combustion was visualized and captured using a combustion endoscopic system. From the captured combustion images, spatial flame distribution was evaluated for butanol-gasoline fuel blends. Furthermore, combustion, emission, and performance characteristics were investigated in a SI engine for the same blends. The engine test results were rationalized from the flame characterization results of butanol-gasoline combustion to improve the fundamental understanding. The experimental outcome is that the flame spread region (%) was found to be higher for butanol blends when compared to sole gasoline fuel. The addition of butanol to gasoline increased the flame speed and consequently increased the combustion burn rate, as well as the pressure and heat release rate within the cylinder. The brake thermal efficiency of the engine increased with increasing butanol concentration in the blend. In addition, the butanol-gasoline blends showed decreased CO and HC emissions when compared to gasoline but reportedly increased NO emission for butanol-blended gasoline blend fuels. Overall, this study concludes that butanol has the potential to be used as a supplement to gasoline due to improved flame and engine characteristics and can be used in the conventional gasoline engine without any major engine modification.
Keywords: Alternate fuels; Butanol; Blends; Endoscopic; Spatial flame distribution